A brief educational intervention can improve nursing students' knowledge of the human papillomavirus vaccine and readiness to counsel - Abbey B. Berenson; Jacqueline M. Hirth; Mihyun Chang; Yong-Fang Kuo; Patricia Richard; Deborah L. Jones (Taylor & Francis Group, 2021)
Provider recommendation is a primary reason for patient uptake of the human papillomavirus (HPV) vaccine. Most provider-focused educational interventions are focused on physicians, even though nurses are also important sources of vaccine-related information for their patients. This study examined whether a HPV educational intervention could improve nursing students' HPV knowledge, beliefs, and comfort with counseling. The same lecture on HPV and HPV vaccination was given to both medical and nursing students. To determine the effects of the lecture, students were asked to complete identical pre- and post-lecture tests with questions on demographics, knowledge, attitudes, and comfort with counseling on the HPV vaccine. Pre- and post-lecture test scores were compared between nursing and medical students to assess whether there were differences in pre-lecture test scores and/or changes in post-lecture test scores. On the pre-lecture tests, fewer nursing students responded correctly to knowledge questions, indicated positive attitudes or comfort with counseling about the HPV vaccine compared to medical students. However, similar frequencies of nursing and medical students responded correctly to knowledge questions and indicated a positive attitude, as well as a high comfort level with counseling on the post-lecture tests. Study results show that integrating lectures in a nursing program curriculum could be a feasible way to increase students' HPV knowledge. Having health-care providers with similar levels of knowledge, attitudes, and comfort with counseling on HPV vaccination is ideal, as all share the responsibility of recommending the vaccine to patients.